A novel approach to Cestrum intermedium (mata-boi): anatomical and physical-chemical characterization, in vitro biological activities, and metabolites of a Brazilian native species - Ellis Marina Szabo; Flavia Deffert; Vanessa Barbosa; Katlin Suellen Rech; Isabel Christina Mignoni Homem; Cristiane Bezerra da Silva; Vinícius Bednarczuk de Oliveira; Marilis Dallarmi Miguel; Obdulio Gomes Miguel (Universidade de São Paulo, 2022)
Abstract The Brazilian native species Cestrum intermedium, known as mata-boi, induces hepatotoxicity and death when ingested by cattle. While most studies on this species focus on toxicological features, our study is the first to describe the anatomy and in vitro biological activities of Cestrum intermedium. We investigated adult leaves and stems by histochemistry, described their anatomy, performed physical-chemical analysis, determined in vitro antioxidant and antimicrobial activities, and identified secondary metabolites. A few noteworthy anatomical features were the anomocytic stomata on the abaxial surface and the absence of trichomes, in addition to the circular shaped petiole with two projections on the adaxial surface. Histochemical analysis showed chemical markers such as alkaloids, usually reported as toxic, and terpenoids. Potassium nitrate (ATR-FTIR) and lupeol palmitate (NMR) were detected on the crude stem extract. Thermogravimetric and physical-chemical analysis provided fingerprint parameters for the species. Minimal Inhibitory Concentration (MIC) assay revealed that Staphylococcus aureus, Staphylococcus epidermidis, and Candida albicans were weakly inhibited by extract samples. Chloroform and ethyl acetate fractions presented high phenolic content, which resulted in in vitro antioxidant activity. These novel features expand the knowledge about this species, considering that previous studies mainly focused on its toxicity. Our study also provided characteristics that may help in avoiding misidentification between Cestrum members, especially when taxonomic keys cannot be employed, as in the absence of flowers and fruits.